Aortic dissection induced by vascular endothelial growth factor inhibitors - Dai, Shuqi; Zhong, Yu; Cui, Hongxia; Zhao, Jin; Li, Su (Frontiers in Pharmacology, 2023)
Vascular endothelial growth factor (VEGF) contributes to angiogenesis and vasculogenesis. The occurrence and progression of tumors are accompanied by the angiogenesis. Vascular endothelial growth factor inhibitors (VEGFI) have been used in anti-tumor treatment. However, aortic dissection (AD) is one of the VEGFI-associated adverse reaction with cute onset, rapid progression, high case fatality rate. We collected case reports of VEGFI related to AD in PubMed and CNKI（China National Knowledge Infrastructure）from inception to April 28, 2022. Seventeen case reports were selected. The medication included sunitinib, sorafenib, pazopanib, axitinib, apatinib, anlotinib, bevacizumab, and ramucirumab. The aim of this review is to discuss the pathology, risk factors, diagnosis and treatment of AD. Vascular endothelial growth factor inhibitors are related to aortic dissection. Although current literature lacks clear statistical evidence on the population, we offer the points to encourage further confirmation of the care for these patients.